2020
DOI: 10.1155/2020/6138438
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids: Key Regulators and Novel Treatment Targets for Type 2 Diabetes

Abstract: Type 2 diabetes mellitus (T2DM), characterized by insulin resistance and unclear pathogenesis, is a serious menace to human health. Bile acids are the end products of cholesterol catabolism and play an important role in maintaining cholesterol homeostasis. Furthermore, increasing studies suggest that bile acids may regulate glucose tolerance, insulin sensitivity, and energy metabolism, suggesting that bile acids may represent a potential therapeutic target for T2DM. This study summarizes the metabolism of bile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 99 publications
2
10
0
Order By: Relevance
“…Hence, measuring metabolite biomarkers in blood has become a new strategy to stratify patients with T2DM complications (7). Interestingly, BAs play certain roles in glucose homeostasis, energy expenditure, and weight control, through receptor-dependent and -independent mechanisms, thereby regulating and maintaining the metabolism of lipids, glucose, and other energy sources, as well as protecting the heart from inflammation, and preventing T2DM and obesity (8)(9)(10). When BA metabolism is altered, imbalanced in lipids, glucose, and energy metabolism may lead to inflammatory metabolic diseases, including T2DM, non-alcoholic fatty liver, and CVDs (11).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, measuring metabolite biomarkers in blood has become a new strategy to stratify patients with T2DM complications (7). Interestingly, BAs play certain roles in glucose homeostasis, energy expenditure, and weight control, through receptor-dependent and -independent mechanisms, thereby regulating and maintaining the metabolism of lipids, glucose, and other energy sources, as well as protecting the heart from inflammation, and preventing T2DM and obesity (8)(9)(10). When BA metabolism is altered, imbalanced in lipids, glucose, and energy metabolism may lead to inflammatory metabolic diseases, including T2DM, non-alcoholic fatty liver, and CVDs (11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BAs work in the body as hormones, being signaling molecules for the expression of genes and regulators of different metabolic paths. The physiological roles of BAs briefly summarized here and comprehensively overviewed by other specialist reports [210][211][212][213][214], opened the field for an extensive investigation of BAs and BADs use in biomedical applications including antimicrobics, anti-cholesterol drugs, regulator of dietary lipid uptake and drug carriers in co-formulations with other molecules (e.g., lipids and polymers). The application possibilities broaden even more when adopting BADs.…”
Section: Discussionmentioning
confidence: 95%
“…It has been well demonstrated that metabolic changes of bile acid may induce glycolipidemia via FXR and TGR5 pathways [5,6]. Alternatively, long-lasting hyperglycemia will influence liver function and secretion of bile acids [7]. erefore, modulating metabolism of bile acids is believed to be a potential target on preventing DM.…”
Section: Introductionmentioning
confidence: 99%